2003
DOI: 10.2527/2003.8161552x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the uterine Mx protein in cyclic and pregnant cows, gilts, and mares1,2

Abstract: Pregnancy and interferon-tau (IFN tau) upregulate uterine Mx gene expression in ewes; however, the only known role for Mx is in the immune response to viral infection. We hypothesize that Mx functions as a conceptus-induced component of the anti-luteolytic mechanism and/or regulator of endometrial secretion or uterine remodeling during early pregnancy. This study was conducted to determine the effects of early pregnancy on uterine Mx expression in domestic farm species with varied mechanisms of pregnancy recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 21 publications
2
56
0
Order By: Relevance
“…In general, these differences are detectable by Day 15 or Day 16 of pregnancy (Forde et al, 2011b;Bauersachs et al, 2012) and the major changes identified include response to a Type I Interferon, of which IFNT is one. This includes the up-regulation of 'classical' interferon-stimulated genes (ISGs) such as ISG15, (Johnson et al, 1998), MX1 and MX2 (Hicks et al, 2003), OAS1, BST2, B2M, CXCL10, STAT1, STAT2, PTX3, EIF4E, USP18 (Forde et al, 2011b) Indeed in the last number of years there have been quite a number of large transcriptomic studies performed on gene expression changes in the endometrium of pregnancy compared with non-pregnant or cyclic heifers. Despite the different platforms used for analysis, breed of animal and different data analysis methods Bauersachs et al (2012) used gene set enrichment analysis to reveal a conceptus-induced signature in the endometrium across numerous studies on Days 15, 16, 17, 18 and 20.…”
Section: Conceptus-induced Effects On the Endometriummentioning
confidence: 99%
“…In general, these differences are detectable by Day 15 or Day 16 of pregnancy (Forde et al, 2011b;Bauersachs et al, 2012) and the major changes identified include response to a Type I Interferon, of which IFNT is one. This includes the up-regulation of 'classical' interferon-stimulated genes (ISGs) such as ISG15, (Johnson et al, 1998), MX1 and MX2 (Hicks et al, 2003), OAS1, BST2, B2M, CXCL10, STAT1, STAT2, PTX3, EIF4E, USP18 (Forde et al, 2011b) Indeed in the last number of years there have been quite a number of large transcriptomic studies performed on gene expression changes in the endometrium of pregnancy compared with non-pregnant or cyclic heifers. Despite the different platforms used for analysis, breed of animal and different data analysis methods Bauersachs et al (2012) used gene set enrichment analysis to reveal a conceptus-induced signature in the endometrium across numerous studies on Days 15, 16, 17, 18 and 20.…”
Section: Conceptus-induced Effects On the Endometriummentioning
confidence: 99%
“…In contrast GM-CSF gene expression was readily stimulated in stromal cells (Emond et al, 2000). Granulocyte chemotatic protein-2, a member of the alpha-chemokine family is also released by cultured endometrial cells in response to IFNτ (Teixeira et al, 1997;Staggs et al, 1998 as during early pregnancy in both endometrium and myometrium Hicks et al, 2003), where steady-state levels of Mx mRNA increase 10-fold above levels observed in cyclic cows by day 15 to 18.…”
Section: Maternal Recognition Of Pregnancy and The Pivotal Role Of Ifmentioning
confidence: 99%
“…Despite the links between progesterone concentrations during early diestrus and fertility in dairy cows as observed in the current study and demonstrated by others (PARR et al, 2012), increasing concentrations by almost 2 ng/mL in CIDR4 and CIDR4+7 cows compared with controls did not result in increased P/AI or reduced pregnancy loss. Mann and Lamming (1999) effects on the endometrium, but also effects on cells in other tissues (HICKS et al, 2003;GIFFORD, 2010). Interferon-τ exits the uterus and reaches the maternal circulation (Oliveira et al, 2008), which induces expression of genes in blood leukocytes (GIFFORD et al, 2008;OLIVEIRA et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The absence of oxytocin receptor in the endometrium prevents the release of luteolytic pulses of PGF, thereby sustaining lifespan of the CL and P4 production (DORNIAK;SPENCER, 2013). In addition to preventing luteolysis, IFN also induces expression of a large number of IFN stimulated genes (ISGs) in the endometrium (HICKS et al, 2003;GIFFORD et al, 2008). Not only endometrial cells express ISGs, but also other tissues, such as peripheral blood mononuclear cells (PBMC).…”
Section: Bastos; Wiltbank 2010)mentioning
confidence: 99%
See 1 more Smart Citation